The Concept of Taboo in French Linguistics (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Taboos and euphemisms remain underexplored in French linguistics, with the terminology still undeveloped. While many articles on this topic have been published in France, and Western linguists are engaging in detailed studies, there are still numerous explanations, terms, and terminological issues in addressing linguistic challenges related to taboos and euphemisms. This article discusses the concepts of “euphemism” and “taboo” their significance, and their role in linguistics, especially within French linguistics.